Integrating Enterprise Resource Planning with the Organizations’ Management Structure for Decision-Making - Atrushi, Diler; Salah, Razwan M.; Ahmed, Nawzat S. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2020)
The unstable situation of some countries in Middle East have caused several crises. Many humanitarians Non-Governmental Organizations (NGOs) intervene to provide services to the affected groups. Good information management may have an effect on the project’s activities and the accuracy of decisions making, especially for organizations that have limited resource. This paper presents the integration of a Management Information System (MIS) and its’ impact in a local organization operating in Duhok City, Kurdistan Region-Iraq (KRI), namely voice of older people and family (VOP Fam). The goal is to increase the quality of humanitarian work through good decision making and data management. Based on the System Usability Scale (SUS) result, the system includes many components as an Enterprise Resource Planning (ERP) and is used by the organization staff for managing and organizing their activities. This system is essential to provide knowledge and can bring together the management and the organization’s senior staff members to make decisions, collect the important information, and allow the donors and the staff of the NGO to follow work timely. The importance of the research lies in its contributes to highlighting the positive impact of integrating a computer-based information system (IS) in conducting humanitarian activities of NGOs in KRI. In addition, it will add a level of reliability to the NGO’s activities data and make it trustworthy. This study has concluded that Integrating IS in organizations can help in decision-making based on analyzing the aggregated data, and prepare more accurate reports in a short period.